ANTI-INFLAMMATORY AND ANTI-NOCICEPTIVE ACTIVITIES OF THE EXTRACTS OF SARGENTODOXA CUNEATA AND ITS EFFECTS ON THE MODEL RATS WITH PELVIC INFLAMMATION - Z. H. Zhou; Q. Weng; J. Zhou; J. H. Zhou (Journal of Animal and Plant Sciences, 2012)
An experiment was conducted to determine the concentration of emodin, the main bioactive content of aqueous extracts of Sargentodoxa cuneata (SC). In addition, the anti-inflammatory, anti-nociceptive activities and the effects of ESC on pelvic inflammation rats were studied. Twenty-one rodents were randomly divided into a SC group, an indomethacin group and a model control group (n=7 in each group) in an ear edema test, a carrageenin-induced paw edema test, a cotton pellet-induced granuloma formation test, and an acetic acid-induced writhing test, respectively. 60 rats were used for pelvic inflammation test. 50 model rats with pelvic inflammation were established and the serum levels of tumor necrosis factor (TNF-α) and interleukin-6 (IL-6) in each group (n=10) were detected with the Enzyme-Linked ImmunoSorbent Assay (ELISA). Analysis of variance (one-way ANOVA) was employed with 5% significance level (P<0.05) and two-tailed tests were used for all hypothesis tests. The concentration of emodin, a bioactive component in the medicinal plant, was determined by High Performance Liquid Chromatography (HPLC). SC extracts had similar anti-inflammatory and anti-nociceptive activities to indomethacin. ESC significantly decreased the levels of TNF-α and IL-6 of the model rats compared with indomethacin. The content of emodin in ESC was 0.2 mg/g.SC, with its strong anti-inflammatory and anti-nociceptive activities, can be used to treat both acute and chronic inflammation and to relieve the associated pain.
Keywords: Sargentodoxa cuneata; anti-inflammatory activities; anti-nociceptive activities; pelvic inflammation